The Diversity of Weaponry in La Tene Culture Burials in Poland and Comments on the Non-burial Find of a Celtic Sword in Rzeszow - Kieca, Piotr (Analecta Archaeologica Ressoviensia, 2022)
The purpose of this work is to create a comprehensive summary of arms originating from Celtic warrior graves in Poland. The largest number of artefacts comes from La Tene culture cemeteries from Lower Silesia, in Sobocisko and Głownin. Individual warrior graves came from Podgaj, Smolec and Wiązow. Other examples of weaponry were found in the Kietrz cemetery in Upper Silesia, with Lesser Poland warrior graves from Iwanowice, Aleksandrowice, and Krakow-Witkowice. From Lesser Poland we also know of alleged graves from Krakow-Pleszow and Krakow-Wyciąże. Some comments about the non-burial find of a Celtic sword from Rzeszow will also be given. A fresh consideration of the source material has corrected the earlier interpretation and reinterpreted some aspects. A new detailed chronology will also be proposed. It will also present a very broad area of connections of Celts residing in Poland.